2020
DOI: 10.3389/fmars.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in Plain Sight: Elopomorph Larvae Are Important Contributors to Fish Biodiversity in a Low-Latitude Oceanic Ecosystem

Abstract: Leptocephalus larvae of elopomorph fishes are a cryptic component of fish diversity in nearshore and oceanic habitats. However, identifying those leptocephali can be important in illuminating species richness in a region. Since the Deepwater Horizon oil spill in 2010, sampling of offshore fishes in the epi-, meso-, and upper bathypelagic depth strata of the northern Gulf of Mexico resulted in 8989 identifiable specimens of leptocephalus larvae or transforming juveniles, in 118 taxa representing 83 recognized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Given their phylogenetic relationship, it is reasonable to believe that bonefish larvae have a similar diet in the wild. This research also supports the theory that leptocephali utilize GAGs for energy because these marine snow components contain the polysaccharide building blocks of the GAGs found within the mucinous pouch of leptocephalus bodies (Moore et al, 2020;Tsukamoto & Miller, 2021).…”
Section: Introductionsupporting
confidence: 80%
“…Given their phylogenetic relationship, it is reasonable to believe that bonefish larvae have a similar diet in the wild. This research also supports the theory that leptocephali utilize GAGs for energy because these marine snow components contain the polysaccharide building blocks of the GAGs found within the mucinous pouch of leptocephalus bodies (Moore et al, 2020;Tsukamoto & Miller, 2021).…”
Section: Introductionsupporting
confidence: 80%
“…A biogeochemical component was added to directly measure the amount of petrogenic contamination in animal organs, muscle tissues, and eggs using polycyclic aromatic hydrocarbons (PAHs) as a proxy (Romero et al, 2018(Romero et al, , 2020. A molecular taxonomy component (DNA barcoding;Hebert et al, 2003) was added to help identify damaged, cryptic, and juvenile specimens where morphological characters do not yet exist or could not differentiate between species (e.g., Moore et al, 2020). The gene sequences analyzed are well established as robust markers for species identification of marine fishes (Ward et al, 2009) and invertebrates (Mantelatto et al, 2018).…”
Section: Survey Approachmentioning
confidence: 99%
“…However, species such as A. balearicum, A. infans, or C. oceanicus showed no evidence of DVM. Some species were also found to use DVM in the Gulf of Mexico (GOM) (Moore et al 2020).…”
Section: Vertical Distributionmentioning
confidence: 99%
“…Some leptocephali were also likely caught at deeper depths at night in the GOM, which is similar to the findings of Ross et al (2007) along the southeast US coast that sampled using similar methodology. Movement of leptocephali to depths below 600 m was clearly documented in the GOM by Moore et al (2020), and some rare species such as synaphobranchids and notacanthids were suggested to remain at those deep depths. This deeper vertical distribution might explain why those two taxonomic groups are the only types of leptocephali that have what is referred to as telescopic eyes (Fig.…”
Section: Vertical Distributionmentioning
confidence: 99%
See 1 more Smart Citation